Climate-Smart Villages: An AR4D approach to scale up climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Agriculture and climate function hand in hand; they also dysfunction hand in hand. Today, 32-39% of global crop yield variability is explained by climate, translating into annual production fluctuations of approximately 2 to 22 million tonnes for major crops such as maize, rice, wheat and soybean [1]. At the same time, agricultural food systems contribute 19- 29% of global greenhouse gas (GHG) emissions [2]. By 2050, the Food and Agriculture Organization of the United Nations (FAO) states that we need to deliver 60% more food for a growing global population with shifting consumption patterns, and all this in a harsher climate [3]. Decreases of around 5% in crop productivity are expected for every 1°C warming above historical levels [4], [5]. These global drivers and trends represent a truly grand challenge that requires concerted action. Climate-smart agriculture (CSA) is proposed as a solution to transform and reorient agricultural systems to support food security under the new realities of climate change. CSA consists of co-achieving three objectives, or pillars, defined as: 1. Sustainably increasing agricultural productivity to support equitable increases in incomes, food security and development; 2. Adapting and building resilience to climate change from the farm to national levels; and 3. Reducing or removing GHG emissions where possible.